Exploratory analysis of mobile network traffic data: a case of a major mobile network operator in Nigeria / Ayisat Wuraola Yusuf-Asaju, Zulkhairi Md Dahalin and Azman Ta’a - Yusuf-Asaju, Ayisat Wuraola; Md Dahalin, Zulkhairi; Ta’a, Azman (2017)
The most effective and common method of assessing mobile network operator’s (MNO) performance is through customer perception, usually gathered using mail, telephone, or internet-based surveys. However, previous studies have observed that the percentage of responses received from customers are extremely low, because customers do not return and complete the surveys at the stipulated time. To overcome the surveys’ drawbacks, recent studies suggested the use of customer experience data obtained from the mobile network traffic. Therefore, this article explores the data collected from a major mobile network operator in Nigeria to determine whether the variables constituted in the dataset can be used in future to evaluate mobile network operator’s performance. The dataset (data tariff, customer complaints and network quality (uplink and downlink throughput) used in this article was gathered from mobile network traffic. The study examined the gathered dataset in R Programming and the result shows that there is a relationship between data tariff and number of internet subscribers, as well as uplink and downlink throughput, which represents the network quality. Overall, the results from the study suggests the dataset can be used to evaluate the MNOs internet service performance to determine mobile internet customers’ satisfaction.